Pengaruh Servant Leadership dan Knowledge Sharing terhadap Kinerja melalui Motivasi Kerja pada Unit Kerja Account Officer PT. Permodalan Nasional Madani Cabang Pematang Siantar - Guntur Guntur; Siti Safaria (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of Servant Leadership and Knowledge Sharing on employee performance both directly and indirectly through work motivation as an intervening variable. The object of this study is the Account Officer work unit at PT. Permodalan Nasional Madani (PNM) Pematang Siantar Branch. The population in this study consisted of 120 employees, in which the entire population was utilized as research samples using the saturated sampling (census) method. Primary data collection was conducted by distributing structured questionnaires using a 5-point Likert scale. The data analysis method employed in this study was Partial Least Squares Structural Equation Modeling (PLS-SEM) operated through SmartPLS software.The results of the structural model analysis indicate that directly, both Servant Leadership and Knowledge Sharing have a positive but non-significant effect on the field operational performance of employees. The effect size ($f^2$) test also confirms that both direct paths fall into the weak category (no effect). Conversely, Servant Leadership and Knowledge Sharing are proven to have a positive and significant effect on increasing employee work motivation, with Knowledge Sharing emerging as the most dominant contributor. Furthermore, work motivation is found to have a direct positive and significant effect on employee performance. The mediation test proves that work motivation plays a crucial role as an intervening variable that fully mediates the effects of Servant Leadership and Knowledge Sharing on employee performance (full mediation). The managerial implication of this study emphasizes that optimizing the performance of Account Officers cannot be achieved instantly merely through leadership styles and knowledge transfer, but must first be internalized to build a solid drive of work motivation.